Prevalence and associated factors of dyslipidemia among the population infected with Helicobacter pylori in Bunia town, Province of Ituri, Democratic Republic of the Congo - KAGORO François, BISINGUREGE; Bafwa Yves, Tibamwenda; wilonja Célestin, Mobali; Jonathan, Ntanyungu; Ngadjole Herman, Chelo; Baba, Amuda; Bassara Godefroy, Nyenke; Chunga Floribet , Kpane; Chuma Micheline, Magapa; Jolie Ruhemura, Mbabazi; Budwanga Baudoin, Manwa; Agasa Salomon, Batina; et al. (Orapuh Journal, 2026)
Introduction Beyond gastric disease, Helicobacter pylori infection has been implicated in metabolic disturbances, including dyslipidemia; however, evidence from eastern Democratic Republic of the Congo remains limited. Purpose This study aimed to determine the prevalence and associated factors of dyslipidemia among individuals infected with H. pylori in Bunia, Ituri Province. Methods This cross-sectional study was conducted at the Evangelical Medical Centre Clinic (CME-Bunia) among 384 adult patients diagnosed with H. pylori infection from January to June 2025. For diagnosis, 0.5 g of stool was diluted in solvent and analyzed using a test strip. For lipid profiling, 5 mL of fasting venous blood was collected, and serum was analyzed for high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C), and triglycerides. A structured questionnaire was used to collect sociodemographic, medical, and lifestyle-related data. Data were analyzed using STATA version 15.2. Logistic regression was used for bivariate and multivariate analyses. Results The prevalence of dyslipidemia was 54.17%. The most frequent lipid abnormalities were combined elevated LDL-C and triglycerides (20.57%), followed by combined low HDL-C and elevated triglycerides (20.05%). Alcohol consumption of more than two glasses per day was associated with a tenfold increased risk of LDL-C disorder after adjustment for other variables (AOR = 9.96, 95% CI [4.56, 21.75], p < .001). Factors significantly associated with HDL-C disorder included age 31–40 years (AOR = 2.72, 95% CI [1.31, 5.64], p = .007), hypertension (AOR = 2.49, 95% CI [1.48, 4.19], p = .001), overweight (AOR = 1.80, 95% CI [1.11, 2.91], p = .008), and obesity (AOR = 2.30, 95% CI [1.24, 4.25], p < .001). Hypertension was associated with triglyceride disorder (AOR = 0.56, 95% CI [0.33, 0.93], p = .026). Smoking was significantly associated with total cholesterol disorder (AOR = 1.86, 95% CI [1.01, 3.42], p = .046). Conclusion Routine lipid profile testing should be introduced for patients diagnosed with H. pylori infection through systematic screening. Community health education should be strengthened to inform both the population and healthcare professionals about potential complications, given the high prevalence of H. pylori infection.